Silicon carbon particles, negative plate and battery

By setting a recess on the surface of silicon carbon particles, the problem of high volume expansion rate and serious surface side reactions during the circulation process of silicon-based negative electrode materials is solved, and the circulation stability and expansion performance of lithium-ion batteries are significantly improved.

CN119890255APending Publication Date: 2025-04-25ZHUHAI COSMX BATTERY CO LTD
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202411972382.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

During the circulation process, existing silicon-based negative electrode materials have problems such as high particle volume expansion rate and serious surface side reactions, which leads to excessive thickness of the SEI film and rapid consumption of active lithium ions, affecting the circulation service life and expansion performance of lithium ion batteries.

Method used

By setting a recess on the surface of silicon carbon particles, the reaction area and reaction sites are increased, the adhesion and stability between silicon carbon particles and the SEI film are improved, and the expansion buffer space is provided for the negative electrode material, thereby improving circulation stability and expansion performance.

Benefits of technology

The cycle stability and expansion performance of silicon-based anode material are significantly improved, the cycle life of lithium-ion batteries is extended, and the energy density of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890255A_ABST
    Figure CN119890255A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to silicon carbon particles, a negative plate and a battery. The invention provides a silicon-carbon particle. The surface of the silicon-carbon particle is provided with a concave part; the number N of the concave parts on the surfaces of the silicon carbon particles is greater than or equal to 1; the diameter of the concave part is 0.05 [mu] m-5 [mu] m; the depth of the recessed part is 10 nm to 5 [mu] m. The sunken parts are arranged on the surfaces of the silicon-carbon particles, so that the cycle stability and the expansion performance of the silicon-based negative electrode material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to silicon-carbon particles, a negative electrode sheet and a battery. Background Art

[0002] With the rapid growth in demand for consumer electronics, electric vehicles and energy storage power stations, traditional graphite materials as battery negative electrodes can no longer meet the requirements of lithium-ion battery energy density in people's daily lives. The use of silicon-based negative electrode materials with higher theoretical lithium storage capacity is an important way to further improve the energy density of lithium-ion batteries.

[0003] However, the existing silicon-based negative electrode materials have the problems of high particle volume expansion rate and serious surface side reactions during the cycle process, which will also cause the silicon-based negative electrode materials to repeatedly generate side reaction layers (SEI films) during the cycle process, resulting in excessive thickness of the side reaction films, and rapid consumption of active lithium ions, thereby accelerating cycle decay, affecting the cycle life of lithium-ion batteries, and deteriorating expansion performance. In addition, studies have found that the side reaction films repeatedly generated on the surface of the existing silicon-based negative electrode materials during the cycle process will also have the problem of shedding, causing the silicon-based negative electrode materials to detach from the formed conductive network and lose activity, and the surface of the exposed fresh silicon-based negative electrode materials will continue to undergo side reactions to generate side reaction layers (SEI films), affecting the cycle stability and expansion performance of lithium-ion batteries. Summary of the invention

[0004] The purpose of the present invention is to overcome the above-mentioned problems existing in the prior art, and provide a silicon-carbon particle, a negative electrode sheet and a battery. The present invention is beneficial to improving the cycle stability and expansion performance of silicon-based negative electrode materials by setting a recessed portion on the surface of the silicon-carbon particle.

[0005] A first aspect of the present invention provides a silicon-carbon particle, wherein the silicon-carbon particle has a concave portion on its surface;

[0006] The number N of the recessed portions on the surface of the silicon-carbon particles is ≥ 1;

[0007] The diameter of the recessed portion is 0.05 μm-5 μm;

[0008] The depth of the recessed portion is 10 nm-5 μm.

[0009] The second aspect of the present invention provides a method for preparing the silicon-carbon particles according to the first aspect of the present invention, the method comprising:

[0010] The porous carbon substrate is immersed in a potassium hydroxide solution for surface treatment, and then the surface treated porous carbon substrate is placed in a vapor deposition furnace, argon gas is introduced and the temperature is increased to 800° C.-1200° C., a concave portion is generated on the surface of the porous carbon substrate, and finally silicon source gas is introduced to deposit nano-silicon in the pores of the porous carbon substrate;

[0011] And / or, placing the porous carbon substrate in a gas phase fluidized bed device for surface fluidization collision treatment, generating a depression on the surface of the porous carbon substrate, and then placing the material subjected to the surface fluidization collision treatment into a gas phase deposition furnace, introducing a silicon source gas, and depositing nano-silicon in the pores of the porous carbon substrate;

[0012] And / or, the porous carbon matrix is ​​placed in a ball mill for ball milling surface modification treatment, a depression is generated on the surface of the porous carbon matrix, and then the material that has undergone the ball milling surface modification treatment is placed in a vapor deposition furnace and silicon source gas is introduced to deposit nano-silicon in the pores of the porous carbon matrix.

[0013] The third aspect of the present invention provides a negative electrode sheet, the negative electrode sheet comprising the silicon-carbon particles described in the first aspect of the present invention and / or the silicon-carbon particles prepared by the method described in the second aspect of the present invention;

[0014] The negative electrode sheet comprises a negative electrode active coating, and the negative electrode active coating comprises the silicon-carbon particles; the ratio N / C of the number N of the recessed portions on the surface of the silicon-carbon particles to the content C% of elemental silicon in the negative electrode active coating is 0.04-10;

[0015] And / or, C is 3%-70%.

[0016] A fourth aspect of the present invention provides a battery, comprising a negative electrode sheet and an electrolyte, wherein the negative electrode sheet is the negative electrode sheet described in the third aspect of the present invention;

[0017] The electrolyte includes a fluorine-containing additive, and the fluorine-containing additive includes at least one of fluoroethylene carbonate, LiBF4, LiCF3SO3, Li(CF3SO2)2N, LiPO2F2 and LiDFOB.

[0018] Through the above technical solution, the present invention has at least the following advantages compared with the prior art:

[0019] The present invention increases the reaction area and reaction sites on the surface of silicon-carbon particles by arranging depressions on the surface of silicon-carbon particles, thereby improving the adhesion and stability between the silicon-carbon particles and the surface SEI film; provides an expansion buffer space for the silicon-carbon negative electrode material, improves the expansion performance of the negative electrode, and is beneficial to significantly improve the cycle stability and expansion performance of the silicon-based negative electrode material.

[0020] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The figure shows the SEM morphology of the outer surface of silicon carbon particles in one example of the present invention;

[0022] Figure 2 The figure shows the SEM morphology of the outer surface of silicon carbon particles in one example of the present invention;

[0023] Figure 3 Shown is a cross-sectional SEM morphology of silicon carbon particles in an example of the present invention;

[0024] Figure 4 Shown is a cross-sectional SEM morphology of silicon carbon particles in an example of the present invention. DETAILED DESCRIPTION

[0025] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0026] A first aspect of the present invention provides a silicon-carbon particle, wherein the silicon-carbon particle has a concave portion on its surface;

[0027] The number N of the recessed portions on the surface of the silicon-carbon particles is ≥1, for example, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29 or 30; the diameter of the recessed portion is 0.05μm-5μm, for example, 0.05μm, 0.06μm, 0.07μm, 0.08μm, 0.09μm, 0.1μm, 0.2μm, 0.3μm, 0.4μm, 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1μm, 1.1μm The thickness of the recessed portion is preferably 1 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, 1 μm, 2 μm, 3 μm, 4 μm, or 5 μm; the depth of the recessed portion is 10 nm-5 μm, for example, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, 1 μm, 2 μm, 3 μm, 4 μm, or 5 μm.

[0028] In the present invention, the number N≥1 of the depressions on the surface of the silicon-carbon particles means that the average number of depressions on the surface of each silicon-carbon particle is ≥1, and does not mean that all silicon-carbon particles have depressions on their surfaces. The test method for the number of depressions on the surface of the silicon-carbon particles can be obtained by counting after observing the SEM image of the silicon-carbon particles. Specifically, the powder of the silicon-carbon particles is first subjected to ultrasound, and after ultrasound, part of the powder is dipped and pasted to the SEM stage, and then tested using a SEM electron microscope. After obtaining the SEM image, take the spherical particles that are completely observable in the image (referring to spherical silicon-carbon particles with complete shape and structure and easy to observe), and read the total number of observable surface depressions × 2 (×2 is because the SEM image can only observe the front side of the spherical silicon-carbon particles, and the number of depressions on the back side cannot be directly observed, so it is determined that it is the same as the number of depressions on the front side, so the total number of observable surface depressions × 2 is used to represent the total number of depressions on the surface of the entire silicon-carbon particle), and then divided by the number of observed particles, which is the average number N of surface depressions per silicon-carbon particle, and the number N needs to be ≥1. Moreover, it should be noted that since the SEM image can only observe the number of depressions on one side surface of the silicon-carbon particle under the front viewing angle, it is impossible to accurately observe the number of depressions on the back side of the same silicon-carbon particle. Therefore, the number of depressions on the surface of the silicon-carbon particle of the present invention only represents the number of depressions on one side surface under the front viewing angle of the SEM test, among which the observable depressions located at the edge of the one side surface under the front viewing angle are also included in the number of depressions of the silicon-carbon particle.

[0029] The present invention provides a recessed portion on the surface of the silicon-carbon particle. On the one hand, the presence of the recessed portion can expose more surface, increase the reaction area and reaction sites on the surface of the silicon-carbon particle, increase the specific surface area of ​​the silicon-carbon particle and the roughness of the surface of the silicon-carbon particle, and improve the adhesion and stability between the silicon-carbon particle and the surface SEI film; on the other hand, the recessed portion has an anchoring effect on the SEI film on the surface of the silicon-carbon particle, which can effectively increase the adhesion area between the surface of the silicon-carbon particle and the SEI film, thereby improving the problem of easy detachment of the SEI film on the surface of the silicon-carbon particle, reducing the repeated generation of new SEI film, and reducing the consumption of active lithium ions, thereby improving the electrochemical performance of lithium-ion batteries, which is beneficial to significantly improve the cycle stability and expansion performance of silicon-based negative electrode materials.

[0030] Furthermore, since the depressions have an anchoring effect on the SEI film, the more the depressions are, the stronger the anchoring effect on the SEI film is, and the depressions can expose more surface area of ​​the silicon-carbon negative electrode material. Therefore, the present invention can further increase the bonding area and anchoring strength between the silicon-carbon particles and the SEI film by controlling the number N≥1 of the depressions on the surface of the silicon-carbon particles, thereby improving the problem of SEI film shedding on the surface of the silicon-carbon particles, reducing the repeated generation of new SEI films, thereby reducing the consumption of active lithium ions, and further improving the cycle stability and expansion performance of silicon-based negative electrode materials.

[0031] Moreover, by controlling the number of depressions N≥1 on the surface of the silicon-carbon particles, the contact area between the silicon-carbon particles and the electrolyte can be increased, which is beneficial to the infiltration and storage of the electrolyte. In addition, it is also beneficial to improve the bonding performance between the silicon-carbon particles and the binder, and to increase the bonding force and bonding strength between the silicon-carbon particles, which helps to further improve the structural stability and cycle stability of the silicon-carbon negative electrode material.

[0032] In one example, the number N of the recessed portions on the surface of the silicon-carbon particles is 4-20.

[0033] In the present invention, the diameter of the recessed portion is 0.05 μm-5 μm, and the depth of the recessed portion is 10 nm-5 μm. Regulating the diameter of the recessed portion within this range is beneficial to the film formation stability of the SEI film on the surface of the silicon-carbon particles and avoiding the detachment of the SEI film; if the diameter of the recessed portion is >5 μm, the overly large recessed portion may cause more serious damage to the surface of the silicon-carbon particles, which may easily lead to more serious rupture of the silicon-carbon particles after cycling, resulting in aggravation of the side reactions in the electrolyte and reducing the cycle stability of the battery; more seriously, if the broken silicon-carbon particles have sharp edges, the diaphragm will be directly pierced, resulting in the risk of internal short circuit of the battery; if the diameter of the recessed portion is <0.05 μm, it will cause its anchoring effect on the SEI film to decrease, and the increased reaction surface area will also be reduced accordingly, which cannot well improve the bonding area and bonding stability of the silicon-carbon particles and SEI, and the improvement effect on the cycle stability and expansion performance of the silicon-carbon negative electrode material is not obvious enough. Therefore, it is necessary to regulate the diameter of the recessed portion within a suitable range.

[0034] In one example, the diameter of the recessed portion is 0.1 μm-2 μm.

[0035] Similarly, regulating the depth of the depression within this range is also beneficial to the film formation stability of the SEI film on the surface of the silicon-carbon particles and preventing the detachment of the SEI film; moreover, the deeper the depth of the depression, the more serious the damage to the surface of the silicon-carbon particles will be. Therefore, it is necessary to regulate the depth of the depression within an appropriate range.

[0036] In one example, the depth of the recessed portion is 50 nm-1 μm.

[0037] The test method for the diameter and depth of the depressed portion on the surface of the silicon-carbon particle can also be obtained by statistically observing the SEM image of the silicon-carbon particle. Specifically, the powder of the silicon-carbon particle is first subjected to ultrasound, and after ultrasound, part of the powder is dipped and pasted to the SEM stage, and then tested using a SEM electron microscope. After the SEM image is obtained, a completely observable spherical particle in the image (referring to a spherical silicon-carbon particle with a complete shape and structure that is easy to observe) is taken, and the diameters of several groups of depressed portions with complete planar shapes on the surface of the particle are measured, and the average value is taken, which is the diameter of the depressed portion on the surface of the silicon-carbon particle; the depth of the observable depressed portion at the edge of the particle surface is measured, and the average value is taken, which is the depth of the depressed portion on the surface of the silicon-carbon particle.

[0038] In the present invention, the average particle size of the silicon-carbon particles is 4 μm-18 μm, for example, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm or 18 μm. The test method for the average particle size of the silicon-carbon particles is to discharge the battery using the silicon-carbon particles as the negative electrode active material from a fully charged state to an empty state, disassemble the battery to remove the negative electrode sheet using the silicon-carbon particles as the negative electrode active material, rinse it in an electrolyte solvent, then wash it with water and dry it, to obtain a negative electrode powder containing the silicon-carbon particles, observe it in a SEM electron microscope, and randomly select 30 complete light-colored silicon-carbon particles in the backscattering mode to measure their diameters, and then obtain the average value of all test results, which is the average particle size of the silicon-carbon particles.

[0039] In one example, the average particle size of the silicon carbon particles is 6 μm-15 μm.

[0040] In the present invention, the median particle size Dv50 of the silicon-carbon particles is 5 μm-25 μm, for example, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm or 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, 21 μm, 22 μm, 23 μm, 24 μm or 25 μm. The median particle size Dv50 of the silicon-carbon particles can be measured using a Malvern particle size tester, and the test steps are as follows: the silicon-carbon particles are dispersed in deionized water containing a dispersant (such as nonylphenol polyoxyethylene ether, with a content of 0.02 wt%-0.03 wt%) to form a mixture, the mixture is ultrasonicated for about 2 minutes, and then placed in a Malvern particle size tester for testing to obtain the median particle size Dv50 of the silicon-carbon particles.

[0041] In one example, the median particle size Dv50 of the silicon carbon particles is 8 μm-20 μm.

[0042] The smaller the average particle size of the silicon-carbon particles, the greater the proportion of the surface area of ​​the depressions on the surface of the silicon-carbon particles to the total surface area of ​​the silicon-carbon particles. Then the surface roughness of a single silicon-carbon particle will be greater, the anchoring effect will be enhanced, the reaction sites will increase, but at the same time, the damage to the surface will be more serious. Therefore, the average particle size of the silicon-carbon particles should not be too small. When the average particle size of the silicon-carbon particles is larger, the proportion of the surface area of ​​the depressions on the surface of the silicon-carbon particles to the total surface area of ​​the silicon-carbon particles will be smaller, the surface roughness of a single silicon-carbon particle will decrease, the anchoring effect will weaken, and the SEI film will still be at risk of falling off from the surface of the silicon-carbon particles in the later stage of the cycle. Therefore, the average particle size of the silicon-carbon particles needs to be reasonably controlled.

[0043] The Dv50 in the median particle size Dv50 of silicon-carbon particles refers to the particle size corresponding to the cumulative particle size distribution volume percentage reaching 50%, that is, the volume percentage of particles with a particle size greater than this value accounts for 50%, and the volume percentage of particles less than this value also accounts for 50%. Therefore, by controlling the median particle size Dv50 of silicon-carbon particles, the contact area between silicon-carbon negative electrode materials and electrolytes can be better controlled when silicon-carbon particles are used as silicon-carbon negative electrode materials, which is beneficial to improving the wettability of electrolytes to negative electrode active materials and the storage capacity of negative electrode active materials to electrolytes; in addition, by controlling the median particle size Dv50 of silicon-carbon particles, it is also beneficial to improve the bonding properties between silicon-carbon particles and binders, improve the bonding force and bonding strength between silicon-carbon particles, and help to further improve the structural stability and electrochemical performance of silicon-carbon negative electrode materials.

[0044] In the present invention, the average sphericity of the silicon-carbon particles is 0.5-1. For example, it is 0.5, 0.65, 0.75, 0.8, 0.85, 0.9, 0.95 or 1; the test method for the average sphericity of the silicon-carbon particles in the present invention may include the following steps: first, the lithium-ion battery is disassembled, the negative electrode sheet is taken out, and it is soaked and rinsed with dimethyl carbonate solvent to remove the lithium salt and electrolyte solvent on the negative electrode sheet, and after drying, the cross-section of the negative electrode sheet is obtained by argon ion cutting. In the backscattering mode of the scanning electron microscope, the silicon-carbon particles show a brighter contrast, and the graphite particles are darker, so it can be processed by image processing software (such as ImagePro Plus) calculates the image of each bright spot particle in the SEM backscattering mode photograph of the negative electrode sheet at a certain magnification (such as 2500 times) to obtain the perimeter and area of ​​each silicon-carbon particle, and calculates the perimeter equivalent radius r1 and area equivalent radius r2 of each particle respectively, then the sphericity of each particle b=r2 / r1, and then the sphericity of each particle is quantitatively weighted averaged to obtain the average sphericity of the silicon-carbon particles in the cross-section of the negative electrode sheet.

[0045] In one example, the average sphericity of the silicon carbon particles is 0.85-1.

[0046] In the present invention, based on the total mass of the silicon-carbon particles, the mass content of elemental silicon is 35%-80%, for example, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75% or 80%; the mass content of elemental silicon in the silicon-carbon particles in the present invention can be obtained by cross-sectional SEM-EDS test analysis of the silicon-carbon particles.

[0047] In the present invention, the silicon-carbon particles include a porous carbon matrix and nano-silicon dispersed in the pores of the porous carbon matrix, and the grain size of the nano-silicon is 1nm-100nm, for example, 1nm, 3nm, 5nm, 6nm, 8nm, 10nm, 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm or 100nm. The negative electrode sheet and battery using the silicon-carbon particles with the above special structure can better alleviate the volume change of the silicon-carbon particles in the later stage of the cycle, and further improve the cycle performance and expansion performance of the battery.

[0048] Further, after the silicon-carbon particles are subjected to a pressure of 377 MPa, the change rate of the median particle size Dv50 is ≤15%, for example, 15%, 14%, 13%, 12%, 11%, 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2%, 1% or 0%. The change rate of the median particle size Dv50 of the silicon-carbon particles after being subjected to a pressure of 377 MPa refers to the ratio of the difference between the median particle size Dv50 of the silicon-carbon particles before and after being subjected to a pressure of 377 MPa to the median particle size Dv50 of the silicon-carbon particles before being subjected to a pressure of 377 MPa. In the present invention, the specific steps of "the silicon-carbon particles are subjected to a pressure of 377 MPa" are as follows: take 1g of silicon-carbon particles (its median particle size Dv50 before being subjected to a pressure of 377 MPa is known), use a powder compactor (for example: Sansi Zongheng 300kN microcomputer-controlled electronic powder compaction testing machine) to apply a pressure of 377 MPa and maintain it at this pressure for 30 seconds, then release the pressure and take out the powder, measure the median particle size Dv50 of the sampled silicon-carbon particles after being subjected to a pressure of 377 MPa, and calculate the change rate of the median particle size Dv50 by the above formula.

[0049] The present invention controls the change rate of the median particle size Dv50 of the silicon-carbon particles to not exceed 15%, thereby screening out silicon-carbon particles with higher compressive strength, so that the silicon-carbon particles used as the negative electrode active material can be guaranteed not to be easily damaged after being rolled by the electrode sheet, thereby avoiding the decrease in the structural stability of the surface of the silicon-carbon particles caused by the provision of the recessed portions, thereby improving the structural stability and cycle performance of the silicon-carbon negative electrode material; moreover, because the silicon-carbon particles have a high compressive strength, the compaction density of the negative electrode sheet containing the silicon-carbon negative electrode material can also be improved, thereby effectively improving the energy density of the lithium-ion battery.

[0050] In one example, the change rate of the median particle size Dv50 of the silicon-carbon particles after being subjected to a pressure of 377 MPa is 2%-8%.

[0051] In the present invention, the sphericity change rate of the silicon-carbon particles after being subjected to a pressure of 377 MPa is ≤10%, for example, 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2%, 1% or 0%. The sphericity change rate of the silicon-carbon particles after being subjected to a pressure of 377 MPa refers to the ratio of the sphericity difference of the silicon-carbon particles before and after being subjected to a pressure of 377 MPa to the sphericity of the silicon-carbon particles before being subjected to a pressure of 377 MPa. By controlling the sphericity change rate of the silicon-carbon particles after rolling to not more than 10%, the silicon-carbon particles can still maintain the original relatively regular spherical morphology of the original geometric shape after rolling, and have a relatively stable structure, thereby increasing the degree of close packing of the silicon-carbon particles and improving the density of the silicon-carbon negative electrode material.

[0052] In one example, the sphericity change rate of the silicon-carbon particles after being subjected to a pressure of 377 MPa is 1%-4%.

[0053] The sphericity of silicon-carbon particles represents the spherical state of silicon-carbon particles. The higher the sphericity, the closer the silicon-carbon particles are to the spherical exemplary spherical state. The testing method is: using image processing software (such as Image Pro Plus) to analyze the image of each particle in the SEM photo of silicon-carbon particles at a certain magnification (such as 2500 times), the circumference and area of ​​each particle are obtained, and the circumference equivalent radius r1 and the area equivalent radius r2 of each particle are calculated respectively. The sphericity of each particle S = r2 / r1, and then the sphericity of each particle is quantitatively weighted averaged to obtain the average sphericity of the silicon-carbon particles. Then, the average sphericity before and after being subjected to a pressure of 377 MPa is calculated to obtain the sphericity change rate of the silicon-carbon particles, %; the sphericity change rate of the silicon-carbon particles (%) = (average sphericity of the silicon-carbon particles before rolling - average sphericity of the silicon-carbon particles after rolling) / average sphericity of the silicon-carbon particles before rolling × 100%.

[0054] The second aspect of the present invention provides a method for preparing the silicon-carbon particles described in the first aspect of the present invention, the method comprising: immersing a porous carbon substrate in a potassium hydroxide solution for surface treatment, then placing the surface-treated porous carbon substrate into a vapor deposition furnace, introducing argon gas and raising the temperature to 800°C-1200°C, generating a depression on the surface of the porous carbon substrate, and finally introducing a silicon source gas to deposit nano-silicon in the pores of the porous carbon substrate.

[0055] Specifically, 30g of porous carbon is immersed in a potassium hydroxide solution with a concentration of 0.8-2mol / L for 6-12h, then taken out, washed and dried, and then the porous carbon is placed in a vapor deposition furnace. First, argon gas is introduced and the temperature is raised to 800-1200°C and kept warm for 2-5h to produce surface pits; the furnace temperature is controlled to 400-500°C, and then monosilane gas with a flow rate of 100-500sccm is introduced for 2-8h; after the end, the introduction of monosilane is stopped, and the temperature is raised to 500-600°C, acetylene gas with a flow rate of 80-150sccm is introduced, the acetylene cracking time is controlled to be 0.5-2h, and the acetylene is stopped and cooled, so that silicon-carbon particles with depressions on the surface can be obtained.

[0056] The second aspect of the present invention provides a method for preparing the silicon-carbon particles described in the first aspect of the present invention, the method comprising: placing a porous carbon matrix into a gas-phase fluidized bed device for surface fluidization collision treatment, generating a depression on the surface of the porous carbon matrix, and then placing the material that has undergone the surface fluidization collision treatment into a gas deposition furnace, introducing a silicon source gas, and depositing nano-silicon in the pores of the porous carbon matrix.

[0057] Specifically, 60g of porous carbon is placed in a gas-phase fluidized bed device and fluidized at high speed at room temperature for 1-5h. After fluidization collision, depressions are generated on the surface of the particles. 30g of the product after fluidization collision is placed in a CVD vapor deposition furnace. First, argon gas is introduced and the temperature is raised to 400-500°C. Subsequently, monosilane gas with a flow rate of 100-500sccm is introduced for 2-8h each. After the introduction of monosilane, the temperature is raised to 500-600°C, and acetylene gas with a flow rate of 80-150sccm is introduced. The acetylene cracking time is controlled to be 0.5-2h. The acetylene is stopped and the temperature is lowered to obtain silicon-carbon particles with depressions on the surface.

[0058] The second aspect of the present invention provides a method for preparing the silicon-carbon particles described in the first aspect of the present invention, the method comprising: placing a porous carbon matrix into a ball mill for ball milling surface modification treatment, thereby generating a depression on the surface of the porous carbon matrix; then placing the material that has undergone the ball milling surface modification treatment into a vapor deposition furnace, introducing a silicon source gas, and depositing nano-silicon in the pores of the porous carbon matrix.

[0059] Specifically, 50g of porous carbon is put into a ball mill for low-speed ball milling for surface modification, the diameter of the zirconia ball is 1mm, the ball-to-material ratio is 1:25, the speed of the planetary ball mill is 10-50rpm, and the ball milling time is 20-40min. 30g of the product after ball milling surface modification is put into a CVD vapor deposition furnace, firstly, argon gas is introduced and the temperature is increased to 400-500°C, and then monosilane gas with a flow rate of 100-500sccm is introduced for 2-8h each; after the end, the introduction of monosilane is stopped, and the temperature is increased to 500-600°C, and acetylene gas with a flow rate of 80-150sccm is introduced, the acetylene cracking time is controlled to be 0.5-2h, and the acetylene is stopped to cool down, so that silicon-carbon particles with depressions on the surface can be obtained.

[0060] The third aspect of the present invention provides a negative electrode sheet, the negative electrode sheet comprising the silicon-carbon particles described in the first aspect of the present invention and / or the silicon-carbon particles prepared by the method described in the second aspect of the present invention, the negative electrode sheet comprising a negative electrode active coating, the negative electrode active coating comprising the silicon-carbon particles; the ratio N / C of the number N of depressions on the surface of the silicon-carbon particles to the content C% of elemental silicon in the negative electrode active coating is 0.04-10, for example, 0.04, 0.06, 0.08, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10.

[0061] In one example, the ratio N / C of the number N of the recessed portions on the surface of each of the silicon-carbon particles to the content C% of elemental silicon in the negative electrode active coating is 2-6.

[0062] In the present invention, the content C% of elemental silicon in the negative electrode active coating is 3%-70%, for example, 3%, 5%, 7%, 9%, 10%, 20%, 30%, 40%, 50%, 60% or 70%. The content C% of elemental silicon in the negative electrode active coating can be measured by an inductively coupled plasma emitter (ICP) method.

[0063] In one example, the content C% of elemental silicon in the negative electrode active coating is 4%-50%.

[0064] The elemental silicon in the negative electrode active coating comes from silicon-carbon particles. If the content C of elemental silicon in the negative electrode active coating is too large, it means that the content of silicon-carbon particles in the negative electrode active coating is large, which is easy to cause the expansion of the negative electrode active coating. Severe expansion may even cause battery failure. Since at least one recessed portion is set on the surface of the silicon-carbon particles, the content of elemental silicon in the negative electrode active coating can be reduced accordingly. Therefore, when the ratio N / C of the number of recessed portions N on the surface of each silicon-carbon particle to the content C of elemental silicon in the negative electrode active coating is within a suitable range, it can ensure that the content C of elemental silicon in the negative electrode active coating will not be excessive, thereby achieving the purpose of inhibiting the expansion of the negative electrode and improving the energy density of the battery, and it can also avoid too many defects on the surface of the silicon-carbon particles due to too many recessed portions being set and damage after multiple cycles, and it can also avoid the repeated generation of new SEI films on the surface of the negative electrode active coating, thereby improving the battery cycle performance; moreover, the setting of the recessed portion structure provides an expansion buffer space for the silicon-carbon negative electrode material, thereby improving the expansion performance of the negative electrode.

[0065] In one example, the negative electrode active coating further includes a carbon-based negative electrode material, and the carbon-based negative electrode material includes at least one of artificial graphite, natural graphite, mesophase carbon microbeads, hard carbon and soft carbon.

[0066] In one example, the negative electrode active coating further includes a negative electrode conductor and a negative electrode binder, wherein the negative electrode conductor includes at least one of conductive carbon black (SuperP) and single-walled carbon nanotubes (SWCNTs), and the negative electrode binder includes at least one of sodium carboxymethyl cellulose (CMC-Na) and styrene-butadiene rubber.

[0067] In one example, based on the total weight of the negative electrode active coating, the weight content of the silicon-carbon particles is 2%-50%, the weight content of the carbon-based negative electrode material is 47%-97%, the weight content of the negative electrode conductor is 0.2%-3%, and the weight content of the negative electrode binder is 0.5%-4%.

[0068] The fourth aspect of the present invention provides a battery, the battery comprising a negative electrode sheet and an electrolyte, the negative electrode sheet is the negative electrode sheet described in the third aspect of the present invention; the electrolyte comprises a fluorine-containing additive, the fluorine-containing additive comprises at least one of fluoroethylene carbonate, LiBF4, LiCF3SO3, Li(CF3SO2)2N, LiPO2F2 and LiDFOB. Silicon-carbon particles are used as silicon-carbon negative electrode materials in the negative electrode active coating of the battery negative electrode sheet, which can effectively improve the cycle capacity retention rate and cycle expansion rate of the battery.

[0069] In the present invention, the battery is fully charged and disassembled after 500 cycles at 25° C., under the conditions of charge and discharge cut-off voltage of 3.0V-4.53V, 1C charging and 1C discharging: the average thickness of the SEI film on the surface of the silicon-carbon particles is 100nm-800nm, for example, 100, 200nm, 210nm, 220nm, 230nm, 240nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm, 550nm, 600nm, 650nm, 700nm, 750nm or 800nm. The average thickness of the SEI film on the surface of the silicon-carbon particles can be calculated by observing the cross-sectional SEM image of the silicon-carbon particles. Specifically, the negative electrode sheet in the battery after the above cycle is disassembled, the powder of the negative electrode active layer of the negative electrode sheet is first subjected to ultrasound, and after ultrasound, part of the powder is dipped and pasted to the SEM stage, and then tested using a SEM electron microscope. After obtaining the SEM image, the spherical particles that are completely observable in the image (referring to spherical silicon-carbon particles whose shape and structure are complete and easy to observe) are taken, and the SEI film thickness at different positions on the surface is measured, and the average value is calculated, which is the average thickness of the SEI film on the surface of the silicon-carbon particles.

[0070] In one example, the average thickness of the SEI film on the surface of the silicon-carbon particles is 300nm-700nm.

[0071] In the present invention, the battery is fully charged and disassembled after 500 cycles at 25°C, with a charge and discharge cut-off voltage of 3.0V-4.53V, 1C charging, and 1C discharging: the content of fluorine in the SEI film on the surface of the silicon-carbon particles is 1%-15%, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14% or 15%. The content of fluorine in the SEI film on the surface of the silicon-carbon particles can be measured by EDS energy dispersive X-ray spectroscopy. The source of fluorine in the SEI film on the surface of the silicon-carbon particles is the fluorine-containing additive in the electrolyte. The fluoride containing fluorine elements in the SEI film is beneficial to improving the stability of the SEI film in the electrolyte and the lithium ion diffusion capacity during the charging and discharging process. Therefore, the present invention can further enhance the improvement effect by regulating the content of fluorine elements in the SEI film on the surface of silicon-carbon particles, thereby enhancing the stability of the SEI film in the electrolyte and avoiding shedding from the silicon-carbon particles, and at the same time enhancing the lithium ion diffusion capacity during the charging and discharging process, thereby being able to construct a stable and highly conductive conductive network, thereby enhancing the cycle stability and expansion performance of the lithium-ion battery.

[0072] In one example, the content of fluorine in the SEI film on the surface of the silicon-carbon particles is 6%-13%.

[0073] In one example, the battery is a lithium-ion battery.

[0074] In one example, the battery further includes a positive electrode sheet, a separator and an electrolyte.

[0075] In one example, the positive electrode sheet includes a positive electrode current collector and a positive electrode active coating located on one side or both sides of the positive electrode current collector, wherein the positive electrode active coating includes a positive electrode active material, a positive electrode conductive agent and a positive electrode binder.

[0076] In one example, the positive electrode active material includes at least one of lithium cobalt oxide, nickel-cobalt-manganese ternary material, lithium iron phosphate, and lithium iron manganese phosphate.

[0077] In one example, the positive electrode conductive agent includes at least one of acetylene black and carbon nanotubes (CNTs).

[0078] In one example, the negative electrode binder includes at least one of polyvinylidene fluoride (PVDF), sodium carboxymethyl cellulose (CMC), styrene butadiene rubber (SBR), and polyacrylic acid (PAA).

[0079] In one example, the electrolyte further includes a lithium salt, a carbonate solvent and other additives.

[0080] In one example, the lithium salt includes at least one of LiPF6, LiBF4, LiSbF6, LiClO4, LiCF3SO3, LiAlO4, LiAlCl4, Li(CF3SO2)2N, LiBOB, LiPO2F2 and LiDFOB.

[0081] In one example, the carbonate solvent includes at least one of ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC).

[0082] In one example, the other additives include one or more of 1,3-propane sultone (PS), 1,3-acrylonitrile lactone (PST), vinyl ethylene carbonate (VEC), adiponitrile (ADN), succinonitrile (SN) and 1,3,6-hexanetrinitrile (HTCN).

[0083] In one example, based on the total weight of the electrolyte, the weight content of the lithium salt is 12%-35%, the weight content of the carbonate solvent is 10%-60%, the weight content of the other additives is 3%-20%, and the weight content of the fluorine-containing additive is 3%-35%.

[0084] The present invention will be described in detail below by way of examples. The examples described in the present invention are only a part of the examples of the present invention, rather than all of the examples. Based on the examples in the present invention, all other examples obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.

[0085] In the following examples, unless otherwise specified, all materials used were commercially available analytical grade.

[0086] The following examples are provided to illustrate the batteries of the present invention.

[0087] Example 1

[0088] Silicon-carbon particles, a negative electrode sheet containing the silicon-carbon particles, and a lithium-ion battery are prepared according to the following method:

[0089] (1) Preparation of ingredients

[0090] Porous carbon: 60 g, particle size Dv10 6.0 μm, Dn50 10 μm, Dv100 28 μm, sphericity S = 0.99;

[0091] Silane gas: monosilane, acetylene gas;

[0092] SiC material: 10 parts by weight;

[0093] Graphite: 86.5 parts by weight of artificial graphite;

[0094] Negative electrode conductive agent: SuperP 0.2 parts by weight; SWCNTs 0.1 parts by weight

[0095] Negative electrode binder: 1.6 parts by weight of sodium carboxymethyl cellulose, 1.6 parts by weight of styrene-butadiene rubber;

[0096] Negative electrode current collector: copper foil thickness is 6 μm;

[0097] (2) Preparation of silicon carbon particles

[0098] 30g of porous carbon was immersed in a 1.5mol / L potassium hydroxide solution for 12h, then taken out, washed and dried, and then placed in a vapor deposition furnace. Argon was first introduced and the temperature was raised to 1000°C and kept for 3h to create surface pits. The temperature was then lowered to 400°C, and then monosilane gas was introduced at a flow rate of 200sccm for 5h each. After the introduction of monosilane, the temperature was raised to 550°C, and acetylene gas was introduced at a flow rate of 120sccm. The acetylene cracking time was controlled to be 1h, and the acetylene was stopped and cooled to obtain the silicon-carbon particles of this embodiment.

[0099] Among them, the outer surface SEM image of the silicon carbon particles is as follows: Figure 1As shown, the number of depressions observed on one side of the silicon-carbon particle is 7, so the number of depressions on the other side is considered to be the same as the number of depressions on the observable surface, and the number N of depressions on the surface of the silicon-carbon particle is 14; the diameter of the depression is 0.5 μm; the depth of the depression is 0.3 μm;

[0100] In addition, the average particle size of the silicon-carbon particles is 7 μm; the median particle size Dv50 of the silicon-carbon particles is 9 μm; after the silicon-carbon particles are subjected to a pressure of 377 MPa, the change rate of the median particle size Dv50 is 5%, and the change rate of sphericity is 3%.

[0101] (3) Preparation of negative electrode sheet

[0102] The silicon carbon particles, artificial graphite, sodium carboxymethyl cellulose, styrene-butadiene rubber, SuperP, and single-walled carbon nanotubes (SWCNTs) prepared in step (2) are mixed in a ratio of 10:86.5:1.6:1.6:0.2:0.1, and deionized water is added to obtain a negative electrode slurry under the action of a vacuum mixer. The negative electrode slurry is evenly coated on the surface of both sides of the negative electrode current collector with a thickness of , and the surface density of the negative electrode slurry coated on the surface of the negative electrode current collector is 11.0 mg / cm 2 The negative electrode current collector coated with the negative electrode slurry was transferred to an oven at 80°C for drying for 12 hours, and then roller pressed (the compaction density was controlled at 1.4-1.8 g / cm 3 within the range of ), and cut to obtain the negative electrode sheet.

[0103] The tested negative electrode sheet negative electrode active coating has an element silicon content C% of 4.9%; at this time, the ratio N / C of the number of depressions N on the surface of the silicon-carbon particles to the element silicon content C% in the negative electrode active coating is 2.86.

[0104] (4) Preparation of lithium-ion batteries

[0105] 1) Preparation of positive electrode

[0106] Lithium cobalt oxide (LCO), polyvinylidene fluoride (PVDF), acetylene black and carbon nanotubes (CNTs) are mixed in a mass ratio of 96:2:1.5:0.5, N-methylpyrrolidone is added, and stirred under the action of a vacuum mixer until a uniform positive electrode slurry is mixed. The positive electrode slurry is evenly coated on an aluminum foil with a thickness of 12 μm. The coated aluminum foil is baked in an oven, then transferred to an oven at 120°C and dried for 8 hours, and then rolled and cut to obtain the desired positive electrode sheet. The size of the positive electrode sheet is smaller than that of the negative electrode sheet, and the reversible capacity per unit area of ​​the positive electrode sheet is 5% lower than that of the negative electrode sheet.

[0107] 2) Negative electrode preparation

[0108] The negative electrode sheet of the above-mentioned embodiment was used.

[0109] 3) Diaphragm

[0110] A polyethylene diaphragm with a thickness of 8 μm was selected.

[0111] 4) Electrolyte

[0112] In a glove box filled with argon (H2O < 0.1ppm, O2 < 0.1ppm), EC / PC / PP / PA were mixed evenly in a mass ratio of 10 / 15 / 55 / 20, and then lithium hexafluorophosphate (LiPF6) with a total mass content of 14.38% based on the total mass content of the electrolyte was quickly added thereto as a lithium salt. After dissolution, 5% fluoroethylene carbonate based on the total mass content of the electrolyte, as well as 4% 1,3-propane sultone (PS), 2% 1,3,6-hexanetrinitrile (HTCN), 2% adiponitrile (ADN), and 1% succinonitrile (SN) were added. The mixture was stirred evenly, and the desired electrolyte was obtained after passing the moisture and free acid tests.

[0113] 5) Preparation of lithium-ion batteries

[0114] The positive electrode sheet of step 1), the separator of step 3), and the negative electrode sheet of step 2) are stacked in order, ensuring that the separator is between the positive and negative electrode sheets to play an isolating role, and then the bare cell is obtained by winding. The bare cell is placed in an aluminum-plastic film shell, and the electrolyte of step 4) is injected into the dried bare cell. After vacuum packaging, standing, formation, shaping, sorting and other processes, the required lithium-ion battery is obtained.

[0115] Example 2

[0116] This Example 2 is carried out with reference to Example 1, with the only difference being that (2) the preparation of silicon-carbon particles is changed, specifically: 60 g of porous carbon is placed in a gas phase fluidized bed apparatus and fluidized at room temperature for 3 h. After fluidization collision, depressions are generated on the surface of the particles. 30 g of the fluidized collision product is placed in a CVD vapor deposition furnace. First, argon is introduced and the temperature is raised to 400°C. Subsequently, monosilane gas is introduced at a flow rate of 200 sccm for 5 h each. After the introduction of monosilane, the temperature is raised to 550°C. Acetylene gas is introduced at a flow rate of 120 sccm. The acetylene cracking time is controlled to be 1 h. The acetylene is stopped and the temperature is lowered to obtain the silicon-carbon particles of this example. For details, see Table 1.

[0117] Example 3

[0118] This Example 2 is carried out with reference to Example 1, with the only difference being that (2) the preparation of silicon-carbon particles is changed, specifically: 50 g of porous carbon is placed in a ball mill for low-speed ball milling for surface modification, the diameter of the zirconia balls is 1 mm, the ball-to-material ratio is 1:25, the speed of the planetary ball mill is 10 rpm, and the ball milling time is 30 min. 30 g of the product after ball milling is placed in a CVD vapor deposition furnace, and argon gas is first introduced and the temperature is increased to 400°C, followed by introduction of monosilane gas at a flow rate of 200 sccm for 5 hours each; after the introduction of monosilane is stopped, the temperature is increased to 550°C, acetylene gas is introduced at a flow rate of 120 sccm, the acetylene cracking time is controlled to be 1 hour, and the acetylene is stopped and cooled to obtain the silicon-carbon particles of this example. For details, see Table 1.

[0119] Example 4 Group

[0120] Example 4 was carried out with reference to Example 2, with the only difference being that (2) the preparation of silicon-carbon particles was changed, specifically: the fluidization temperature, fluidization gas flow rate and fluidization time of the gas phase fluidized bed equipment were adjusted so that the number N of depressions on the surface of the silicon-carbon particles, the diameter and depth of the depressions were changed. For details, please refer to Table 1.

[0121] Example 5 Group

[0122] Example 5 was carried out with reference to Example 2, with the only difference being that (1) the component preparation was changed, specifically: the particle size of the raw porous carbon was changed so that the average particle size and median particle size Dv50 of the silicon carbon particles were changed. For details, see Table 1.

[0123] Example 6 Group

[0124] Example 6 was carried out with reference to Example 2, with the only difference being that (3) the preparation of the negative electrode sheet was changed, specifically: the amount of silicon-carbon particles added to the negative electrode active coating was changed, so that the content C% of elemental silicon in the negative electrode active coating was changed, as shown in Table 1 for details.

[0125] Example 7 Group

[0126] Example 7 was carried out with reference to Example 2, with the only difference being that (2) the preparation of silicon-carbon particles was changed, specifically: the number N of depressions on the surface of the silicon-carbon particles, the diameter and depth of the depressions, and the content C% of elemental silicon in the negative electrode active coating were simultaneously changed. For details, please refer to Table 1.

[0127] Comparative Example 1

[0128] Comparative Example 1 was carried out with reference to Example 2, except that (2) the preparation of silicon-carbon particles was changed. Specifically, instead of placing the raw porous carbon in a gas-phase fluidized bed to prepare depressions, 30 g of porous carbon was directly placed in a CVD vapor deposition furnace, and argon gas was first introduced and the temperature was raised to 400° C., followed by introduction of monosilane gas at a flow rate of 200 sccm for 5 h each; after the introduction of monosilane was stopped, the temperature was raised to 550° C., acetylene gas at a flow rate of 120 sccm was introduced, the acetylene cracking time was controlled to be 1 h, and the acetylene was stopped and cooled to obtain silicon-carbon particles without depressions. The SEM image of the outer surface of the silicon-carbon particles is as follows: Figure 2 shown.

[0129] Comparative Example 2

[0130] Comparative Example 2 was carried out with reference to Example 2, with the only difference being that (2) the preparation of silicon-carbon particles was changed, specifically: the fluidizing temperature, fluidizing gas flow rate and fluidizing time of the gas phase fluidized bed equipment were adjusted so that the number of depressions on the surface of the silicon-carbon particles N = 1, and the diameter of the depressions = 7 μm, as shown in Table 1 for details.

[0131] Comparative Example 3

[0132] Comparative Example 3 was carried out with reference to Example 2, with the only difference being that (2) the preparation of silicon-carbon particles was changed, specifically: the fluidization temperature, fluidization gas flow rate and fluidization time of the gas phase fluidized bed equipment were adjusted so that the number of depressions on the surface of the silicon-carbon particles N = 1, and the depth of the depressions = 7000 nm. For details, see Table 1.

[0133] Table 1

[0134]

[0135] Test Case

[0136] 1) Capacity retention rate test after cycling

[0137] At room temperature, the batteries prepared in the above embodiments and comparative examples were charged to 4.53V at 0.5C or 3C constant current and constant voltage, and cut off at 0.05C, and then discharged to 3.0V at 0.5C, and cycled for 500 cycles. The capacity retention rate after 500 cycles was calculated by the following formula: capacity retention rate = termination capacity / initial capacity*100%.

[0138] 2) Expansion rate test after cycle

[0139] At room temperature, the batteries prepared in the above embodiments and comparative examples were charged to 4.53V at 0.5C or 3C constant current and constant voltage, cut off at 0.05C, and then discharged to 3.0V at 0.5C, and cycled to 500 cycles, calculated by the following formula: expansion rate = (THK1-THK0) / THK0×100%; wherein THK0 is the thickness of the initial 3.85V battery measured by 600gPPG, and THK1 is the thickness of the fully charged battery after cycling.

[0140] 3) Thickness of SEI film on particle surface after cycling

[0141] At room temperature, the batteries prepared in the above embodiments and comparative examples were charged to 4.53V at 0.5C or 3C constant current and constant voltage, and cut off at 0.05C, and then discharged to 3.0V at 0.5C and cycled for 500 weeks. After the cycle, the fully charged cells were disassembled, the pole pieces with intact appearance were taken and sealed, the cross-section of the negative pole piece was polished with Ar particles, and the SEM backscattering mode was selected for observation. The light-colored area of ​​the particles was the high atomic number element Si, and the dark-colored area was the side reaction product SEI composed of low atomic number elements. The state of the SEI on the particle surface was observed by SEM and the thickness of the SEI film on the particle surface was measured.

[0142] 4) Characterization of fluorine in SEI film on particle surface after cycling

[0143] At room temperature, the batteries prepared in the above embodiments and comparative examples were charged to 4.53V at 0.5C or 3C constant current and voltage, and cut off at 0.05C, and then discharged to 3.0V at 0.5C and cycled for 500 cycles. After the cycle, the fully charged cells were disassembled, and the pole pieces with intact appearance were taken. The CP pole pieces were scanned by EDS (elemental analysis) using SEM. The scanning results showed that the SEI layer on the surface of the particles contained more F elements, and the mass content of fluorine element in the SEI film was obtained.

[0144] The test results of the above test examples are recorded in Table 2.

[0145] Table 2

[0146]

[0147]

[0148] According to the test method of the above test example, the batteries prepared in the above examples and comparative examples were charged to 4.53V at 0.5C or 3C constant current and constant voltage at room temperature, and then discharged to 3.0V at 0.5C. After 500 cycles, the cross-sectional SEM morphology of the silicon-carbon particles in Example 1 is as follows: Figure 3 As shown, the SEI film did not fall off. The cross-sectional SEM morphology of the silicon-carbon particles in Comparative Example 1 is shown in Figure 4 As shown in the figure, the SEI film is thick, and the SEI film is fractured and falls off near the outside.

[0149] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A silicon-carbon particle, characterized in that: The silicon-carbon particles have a concave portion on their surface; The number N of the recessed portions on the surface of the silicon-carbon particles is ≥ 1; The diameter of the recessed portion is 0.05 μm-5 μm; The depth of the recessed portion is 10 nm-5 μm.

2. The silicon-carbon particles according to claim 1, wherein The number N of the recessed portions on the surface of the silicon-carbon particles is 4-20; And / or, the diameter of the recessed portion is 0.1 μm-2 μm; And / or, the depth of the recessed portion is 50 nm-1 μm.

3. The silicon-carbon particles according to claim 1 or 2, wherein: The average particle size of the silicon carbon particles is 4 μm-18 μm; preferably 6 μm-15 μm; And / or, the median particle size Dv50 of the silicon-carbon particles is 5 μm-25 μm; preferably 8 μm-20 μm; And / or, the average sphericity of the silicon-carbon particles is 0.5-1; preferably 0.85-1; and / or, based on the total mass of the silicon-carbon particles, the mass content of elemental silicon is 35%-80%; And / or, the silicon-carbon particles include a porous carbon matrix and nano-silicon dispersed in pores of the porous carbon matrix, and the grain size of the nano-silicon is 1 nm-100 nm.

4. The silicon-carbon particles according to claim 3, wherein The change rate of the median particle size Dv50 of the silicon-carbon particles after being subjected to a pressure of 377 MPa is ≤15%, preferably 2%-8%.

5. The silicon-carbon particles according to claim 3, wherein The sphericity change rate of the silicon-carbon particles after being subjected to a pressure of 377 MPa is ≤10%, preferably 1%-4%.

6. A method for preparing the silicon-carbon particles according to any one of claims 1 to 5, characterized in that: The method comprises: The porous carbon substrate is immersed in a potassium hydroxide solution for surface treatment, and then the surface treated porous carbon substrate is placed in a vapor deposition furnace, argon gas is introduced and the temperature is increased to 800° C.-1200° C., a concave portion is generated on the surface of the porous carbon substrate, and finally silicon source gas is introduced to deposit nano-silicon in the pores of the porous carbon substrate; And / or, placing the porous carbon substrate in a gas phase fluidized bed device for surface fluidization collision treatment, generating a depression on the surface of the porous carbon substrate, and then placing the material subjected to the surface fluidization collision treatment into a gas phase deposition furnace, introducing a silicon source gas, and depositing nano-silicon in the pores of the porous carbon substrate; And / or, the porous carbon matrix is ​​placed in a ball mill for ball milling surface modification treatment, a depression is generated on the surface of the porous carbon matrix, and then the material that has undergone the ball milling surface modification treatment is placed in a vapor deposition furnace and silicon source gas is introduced to deposit nano-silicon in the pores of the porous carbon matrix.

7. A negative electrode sheet, characterized in that: The negative electrode sheet comprises the silicon-carbon particles according to any one of claims 1 to 5 and / or the silicon-carbon particles prepared by the method according to claim 6; The negative electrode sheet comprises a negative electrode active coating, and the negative electrode active coating comprises the silicon-carbon particles; the ratio N / C of the number N of the recessed portions on the surface of the silicon-carbon particles to the content C% of elemental silicon in the negative electrode active coating is 0.04-10; And / or, C% is 3%-70%.

8. A battery, characterized in that: The battery comprises a negative electrode sheet and an electrolyte, wherein the negative electrode sheet is the negative electrode sheet according to claim 7; The electrolyte includes a fluorine-containing additive, and the fluorine-containing additive includes at least one of fluoroethylene carbonate, LiBF4, LiCF3SO3, Li(CF3SO2)2N, LiPO2F2 and LiDFOB.

9. The battery according to claim 8, wherein The battery was fully charged and disassembled after 300 cycles at 25°C, with a charge and discharge cut-off voltage of 3.0V-4.53V, 1C charging, and 1C discharging: The average thickness of the SEI film on the surface of the silicon-carbon particles is 100nm-800nm, preferably 300nm-700nm.

10. The battery according to claim 8, wherein The content of fluorine element in the SEI film on the surface of the silicon-carbon particles is 1%-15%.

Citation Information

Cited By

  • Negative plate and battery

    CN121938848A

  • A negative electrode sheet and a battery

    CN121938848B

  • Silicon-carbon particle, negative electrode sheet, and battery

    WO2026145536A1

  • Negative electrode sheet and battery

    WO2026179801A1